2017
DOI: 10.2298/psi1703271v
|View full text |Cite
|
Sign up to set email alerts
|

Learning to draw: Does the inversion technique work?

Abstract: Several methods for teaching draftsmanship include exercises based on Edward?s ?inversion? technique, the practice of copying from upside-down originals. We tested the technique by asking 40 artistically untrained participants to copy either upright or upside-down drawings of a face or a car. Our results indicate that participants were faster when copying the car in comparison to the face, but not when copying upside-down in comparison to upright images. In addition, they were more accurate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In Studies 2 and 3, we assessed differences in absolute drawing errors between upright and upside-down drawings in the attempt to replicate prior findings (Day & Davidenko, 2018; Ostrofsky, Kozbelt, Cohen, et al, 2016; Viviani & Bruno, 2017); and for the first time, between upright and sideways drawings. With respect to the comparison of upright and upside-down observation-based drawings, we replicated in Study 2 the prior finding that reproductions of the eye-mouth distance were less accurate in upside-down drawings relative to upright drawings, and that there were no significant differences between these two types of drawings with respect to errors in reproducing the nose-mouth distance and the interocular distance (Ostrofsky, Kozbelt, Cohen, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Studies 2 and 3, we assessed differences in absolute drawing errors between upright and upside-down drawings in the attempt to replicate prior findings (Day & Davidenko, 2018; Ostrofsky, Kozbelt, Cohen, et al, 2016; Viviani & Bruno, 2017); and for the first time, between upright and sideways drawings. With respect to the comparison of upright and upside-down observation-based drawings, we replicated in Study 2 the prior finding that reproductions of the eye-mouth distance were less accurate in upside-down drawings relative to upright drawings, and that there were no significant differences between these two types of drawings with respect to errors in reproducing the nose-mouth distance and the interocular distance (Ostrofsky, Kozbelt, Cohen, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in Studies 2 and 3, we assessed whether observation-based drawing errors differ or not between reproductions of upright-versus rotated-oriented models. Despite art instructors' claims that drawing upside-down models improves drawing quality (e.g., Edwards, 2012); past research has demonstrated that upside-down model rotation either impairs or has no effect on the drawing of spatial relationships between facial features (Cohen & Earls, 2010;Day & Davidenko, 2018;Ostrofsky, Kozbelt, Cohen, et al, 2016;Viviani & Bruno, 2017).…”
mentioning
confidence: 99%